The Relationship Between Environmental, Social, Governance (ESG) Factors and Retail Investors’ Investment Decisions: Evidence From PT Bank Central Asia Tbk (BBCA) - Intan Paramithasari, Tjokorda Istri; Anggoro, Yudo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study investigates the influence of Environmental, Social, and Governance (ESG) factors on retail investors’ investment decisions in PT Bank Central Asia Tbk (BBCA), Indonesia’s largest private bank. The research aims to analyze the effect of each ESG dimension on investment decision-making and to test the moderating role of investment horizon. A quantitative explanatory approach was employed using a structured questionnaire distributed to 175 retail investors who own BBCA shares. The collected data were analyzed using multiple regression and moderated regression with 2,000-sample bias-corrected and accelerated (BCa) bootstrapping to ensure the robustness of the results. The findings show that ESG factors collectively have a positive and significant effect on investment decisions. Among the three dimensions, Governance is the only significant factor, emphasizing the importance of transparency, accountability, and ethical management in building investor trust. Environmental and Social dimensions have positive but insignificant effects, while investment horizon does not significantly moderate the relationship. The study concludes that credible governance practices serve as the strongest ESG signal influencing investor behavior and recommends that BCA enhance ESG communication through interactive portals and social media to strengthen transparency and investor engagement.